Defining employment discrimination in Malaysian legal context - Abdul Wahab, Harlida; Mahmod, Nik Ahmad Kamal (Universiti Putra Malaysia, 2020)
Discrimination deprives people of equal rights. It creates barriers to employment and resulted in people's right to full participation in the workplace jeopardised. Consequently, people are denied jobs, confined to certain occupations, offered with lower pay, refused promotion and increment, and so on. The grounds for discrimination are commonly owing to their 'physical appearance' such as sex, race, the colour of skin, faith or religion regardless of the capabilities and abilities to performing the job. Therefore, promoting equality by eliminating various forms of discrimination is essential. This paper is looking at employment discrimination from the legal perspective. Generally, the meaning and elaboration of employment discrimination together with its types and grounds are presented by considering other jurisdictions, particularly the United Kingdom, that has her antidiscrimination law namely Equality Act 2010. Owing to the absence of anti-discrimination law in Malaysia, the authors founded the discussion on this Act of the UK while the analysis of employment discrimination in Malaysia is presented by analysing the related court cases. The paper showed that employment discrimination did occur in Malaysia. This paper is expected to give some limelight and reflection on the issues concerned principally in defining employment discrimination within the Malaysian legal context.